The Correlation between Lecturers' Teaching Styles in the Learning Process and the Duration of Study of Medical Students at Pattimura University, Ambon - Irwinda A Sahiman (PT Pubsains Nur Cendekia, 2026)
Background: Lecturers’ teaching styles are essential in medical education, influencing academic success and study completion, although previous studies show inconsistent relationships with students’ study duration. Aims: To analyze the distribution of lecturers’ teaching styles and to examine the relationship between lecturers’ teaching styles and the study duration of students at the Faculty of Medicine, Pattimura University. Methods: This study employed a quantitative design with a correlational analytic approach. The sample consisted of 118 respondents. Lecturers’ teaching styles were categorized into three levels: fair, good, and very good. Descriptive analysis was used to determine the distribution of teaching styles, while Spearman’s rank correlation test was applied to examine the relationship between lecturers’ teaching styles and students’ study duration. Results: The findings revealed that the majority of lecturers were classified as having very good teaching styles (64.4%), followed by good (33.9%), while only a small proportion were categorized as fair (1.7%). Spearman’s correlation analysis showed a correlation coefficient of r = 0.170 with a significance value of p = 0.065, indicating a positive but weak relationship between lecturers’ teaching styles and students’ study duration. Conclusions: Lecturers’ teaching styles show a weak positive relationship with study duration, while motivation, curriculum workload, and facilities exert greater influence.